Using Resin Infiltration Technique and Direct Composite Restorations for the Treatment of Carious Lesions with Different Depths - İsmail Serhat Sadıkoğlu (Hindawi Limited, 2023)
Minimally invasive treatment methods are of special interest in restorative dental practice, with numerous methods emerging in the last decade. Such methods are being developed to encompass various applications, an important one being the detection and treatment of caries in the early stages. White spot lesions are the earliest visible stage of the caries process. These lesions have a chalky, opaque appearance, which results in esthetic dissatisfaction. In contrast to the principles of minimally invasive dentistry, considerable amounts of sound tooth structure need to be sacrificed to get rid of these lesions. Therefore, caries infiltration has been introduced as an alternative treatment option for non-cavitated lesions. The resin infiltration technique only works in non-cavitated lesions. Replacement of lost dental tissue with resin composites remains the mainstay therapy in cases with cavity formation. This case report describes a case of caries with lesions of varying depths. In such cases, a combination of treatment methods may be used to provide satisfying esthetics with a minimally invasive approach.